Resistance and Manipulated Aestheticism in Baldwin's If Beale Street Could Talk: Harlem as Home for African Americans - Batool, Jovairiah; Parveen, Sabahat; Akram, Tayyaba (Pakistan Journal of Humanities and Social Sciences, 2023)
This paper aims to achieve the very basic idea of home and also creates the promotion of aestheticism in which striving and struggle of blacks will be discussed. Home is a place whereby productivity is born. This paper will shed light on the productive lives of black which are surrounded by racism. When home or homeland is discussed, then the concepts of unity, peace, financial benefits and issues of identity are solved. This paper will also discuss that how the fate of black nation is changed in the home (Harlem) and the sense of having shelter manipulates art and aestheticism of blacks. The elements of resistance against white are strengthened, when the need of home is fulfilled, as in the Harlem of Renaissance. Home gives identity and that is the reason of flourishing nation. By using African American Criticism, this paper will talk about all the aspects of Harlem as home for blacks by explaining the fictious characters of Baldwin’s If Beale Street Could Talk (2019) and it will explain that how the Negro’s movements have been affluenting in Harlem and this paper will connect struggle and strive of blacks with the characters of novella.